Direct endoscopic necrosectomy: Pilot study of a new dedicated device - Ligresti, Dario; Binda, Cecilia; Fugazza, Alessandro; Maida, Marcello; Traina, Mario; Anderloni, Andrea; Fabbri, Carlo; Tarantino, Ilaria (Endoscopy International Open, 2024)
Background and study aims Direct endoscopic necrosectomy (DEN) represents the first-line treatment for walled-off necrosis (WON). However, DEN has a non-negligible rate of overall adverse events (AE) and is time-consuming due to the lack of dedicated devices. This pilot study was designed to evaluate the feasibility and safety of a novel dedicated device for DEN named Necrolit.Patients and methods In this multicenter retrospective analysis,16 patients with WON who underwent DEN using Necrolit were compared with a control group treated with non-dedicated devices. Technical success, AEs, clinical success, number of procedures per patient, procedure time, and length of hospital stay were evaluated. Necrolit technical performance indicators were also studied.Results Technical success was obtained in all patients in both groups. In the Necrolit group, the overall AE rate was 10.1% vs. 15.9% in the control group. Clinical success was 100% in the Necrolit group vs. 81.3% in the control group. Patients treated with Necrolit underwent a slightly lower mean number of procedures (4.1 ± 2.3 vs. 5.1 ± 1.9) with comparable mean procedure time (67.8 ± 39 minutes vs. 70.1 ± 32.6 minutes). Mean duration of hospital stay was 39.4 days (± 30.9) in the Necrolit group vs. 43 days (± 29.4) in the control group. Device-related technical performance was rated positively.Conclusions DEN with Necrolit appears feasible and safe.
Keywords: Endoscopic ultrasonography; Intervention EUS; Pancreas